Aspectos sustanciales de la responsabilidad fiscal en Colombia (2007)
The present article’s objective is to assess the substantive element of Fiscal Responsibility, which isfounded on the basic conditions required for the application of fiscal control. In the contemporary world the application of fiscal control is understood as a model that developsthe democratic principles, and thus, it goes beyond the historical framework of a three-branchedpower.Within this framework, the constitutional and legal context of fiscal responsibility will be examined,establishing the relationships between fiscal management, fiscal surveillance and fiscal responsibility.The essential features of fiscal responsibility will be deduced from this framework, and those willallow to distinguish between said responsibility and other types of responsibilities that have to beassumed by the public servant.Finally, it is necessary to analyze the constituting elements of, without which it is impossible toidentify this responsibility